Selection of resin and aggregates for particulate polymer concrete machine tool structures-A review. (2021) - Venkata Ramana, Mula; Thyla, P.R.; Mahendrakumar, N.; Praveena, K.
Abstract: Precision machine tools are the most essential machines in manufacturing sector. Performance of precision machines in terms of high accuracy and high productivity is depending on the static, dynamic and thermal characteristics of the machine tools. Use of particulate polymer composites in machine tool applications improves the dynamic characteristics due to their high damping capacity than conventional materials like cast-iron. Literature survey conducted for selecting aggregates, resins and other fillers for polymer matrix composites for machine tool structures presented in this article. Aggregate types and sizes, effective resin content and other filler materials will influence the mechanical and thermal characteristics of machine tool structures. Aggregate sizes will influence the presence of air voids in prepared composite which influences the damping capacity. Bond strength between resin and particulates depend on effective resin content. Type and volume fraction of resin, hardener chemical reaction impacts the curing time. Manufacturing of machine tools is based on stiffness, strength and damping capacity is criteria for effective design. Particulate polymer concrete development is crucial to achieve required characteristics. In this article design challenges and solutions for designers to develop particulate composites for machine tool structures have been presented by review.